Cover Feature: Cationic Chalcogenoviologen Derivatives for Photodynamic Antimicrobial Therapy and Skin Regeneration (Chem. Eur. J. 59/2019). Issue 59 (18th September 2019) - Zhou, Kun; Tian, Ran; Li, Guoping; Qiu, Xinyu; Xu, Letian; Guo, Mengying; Chigan, Dongdong; Zhang, Yanfeng; Chen, Xin; He, Gang
Abstract : A new cationic chalcogenoviologen‐based photosensitizer with functional side chains that use close‐range electrostatic binding to eliminate inefficient ROS delivery and destroy the membranes of bacteria has been designed. This biocompatible and nontoxic system provided a new antibacterial mechanism that led to improved PDT efficiency as well as excellent anti‐inflammatory and neovascularization activities that accelerated skin regeneration. More information can be found in the Communication by X. Chen, G. He, et al. on page 13472 .